Media Pembelajaran dalam Presfektif Hadis - Juniarti Iryani; Erwin Hafid; Arifuddin Ahmad (CV Putra Publisher, 2023)
The purpose of this research is to discuss the Islamic perspective on instructional media from the perspectives of Hadith and the Qur'an. The research method used is qualitative research with library research. The data was gathered through literature research, consisting of primary sources such as journals and other relevant readings related to thematic Hadith studies. The data management is entirely qualitative because the data encountered is in the form of verbal statements. The analysis method used is an